Immunological Evaluation on Potential Treatment Window for Hospitalized COVID-19 Patients - Yuan, Jing; Kou, Shanglong; Liang, Yanhua; Lan, JianFeng; Li, Xiaohe; Zeng, Lijiao; Zou, Rongrong; Liu, Yingxia; Liu, Lei; Pan, Yanchao (Journal of inflammation research, 2020)
Novel coronavirus disease has become such an escalating epidemic that the exponential growth of infected patients has overloaded the health-care systems in many countries. Determination of early assessments for patients with a risk of clinical deterioration would benefit the management of COVID-19 outbreaks. A total of 214 confirmed COVID-19 patients were enrolled from January 11th to February 11th 2020. Medical records including laboratory parameters, clinical outcomes and other characteristics of the admitted patients were analyzed retrospectively. The critical patients experienced a significantly prolonged onset-admission interval and presented with lymphopenia ( =-0.547, =0.015) and lower albumin level ( <0.001) 6 days after symptom onset. Early admission of critical patients significantly reduced the duration of hormone therapy. Starting from 9 days of hospital stay, the reduced lymphocyte counts exhibited linear growth. Furthermore, on days 9 and 12, significant correlations were demonstrated between immunological manifestations and duration of hormone therapy in critical patients, and length of hospital stay in severe patients. In addition, the virus negative conversion rate was more significantly correlated with increased lymphocytes in critical patients. Early intervention, within 6 days of symptom onset, benefited patients' recovery from critical illness. The 9-12 days of hospital care represented a valuable window during which to evaluate the therapeutic effects on physical recovery and virus clearance.